A new multidisciplinary non-destructive protocol for the analysis of stony meteorites: gamma spectroscopy, neutron and muon techniques supported by Raman microscopy and SEM-EDS. Issue 2 (25th November 2022) - Rossini, Riccardo; Di Martino, Daniela; Agoro, Toluwalase; Cataldo, Matteo; Gorini, Giuseppe; Hillier, Adrian D.; Laubenstein, Matthias; Marcucci, Giulia; Musa, Maya; Riccardi, Maria Pia; Scherillo, Antonella; Clemenza, Massimiliano
Abstract : The physical and chemical characterisation of meteorites is of paramount importance in the study of the formation of the Solar System. Abstract : The physical and chemical characterisation of meteorites is of paramount importance in the study of the formation of the Solar System. In this work we show the feasibility of a complete set of non-destructive measurements to perform such a characterisation using a stony meteorite as a mock-up sample. The identification of the sample as a meteorite was performed by means of gamma ray spectrometry, which identified the presence of cosmogenic 26 Al. Time-of-Flight Neutron Diffraction (ToF-ND) enabled the mineralogical phase quantification and the analysis of the presence of strains and substitutions in each mineral. Neutron Resonance Capture Analysis (NRCA), Neutron Resonance Transmission Imaging (NRTI) and Muonic Atom X-Ray Spectroscopy (MAXRS) allowed a study of the presence and the space distribution of certain elements. Furthermore, micro-Raman Spectroscopy (μRS) and Scanning Electron Microscopy with Energy-Dispersive X-ray Spectroscopy (SEM-EDS) were also considered in order to validate the protocol.